2020
DOI: 10.24191/mjoc.v5i1.6760
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Between Univariate and Bivariate Time Series Models for Crude Palm Oil Industry in Peninsular Malaysia

Abstract: The main purpose of this study is to compare the performances of univariate and bivariate models on four-time series variables of the crude palm oil industry in Peninsular Malaysia. The monthly data for the four variables, which are the crude palm oil production, price, import and export, were obtained from Malaysian Palm Oil Board (MPOB) and Malaysian Palm Oil Council (MPOC). In the first part of this study, univariate time series models, namely, the autoregressive integrated moving average (ARIMA), fractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The forecasting results for imports showed that the ARIMA (2,1,2) model had the best fit. the ARIMA models, ARFIMA models and autoregressive (ARAR) algorithm were used for in order to forecast Malaysia imports (Wee Mah and Nanyan, 2020). Merous and Asfaria (2017), analysed the imports of Malaysia for goods and used multiple regression model, Input-output model, composite model and ARIMA model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The forecasting results for imports showed that the ARIMA (2,1,2) model had the best fit. the ARIMA models, ARFIMA models and autoregressive (ARAR) algorithm were used for in order to forecast Malaysia imports (Wee Mah and Nanyan, 2020). Merous and Asfaria (2017), analysed the imports of Malaysia for goods and used multiple regression model, Input-output model, composite model and ARIMA model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While Akdi et al (2020) forecasted daily electricity consumption in Turkey using ARIMA and harmonic regression models for the amounts consumed each day of electricity in Turkey between 2012 and 2016. Researched by Wee Mah and Nanyan (2020) examined results of a few models using four-time exponential series techniques used in Peninsular Malaysia's crude palm oil business. The results indicated that the bivariate models outperformed the univariate models for the production and export of crude palm oil based on the forecast accuracy criteria that were used.…”
Section: Literature Reviewmentioning
confidence: 99%